(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Pregelatinized starches exhibit good swelling and flow properties, imparting fast disintegration time but low mechanical strength in tablets. On the other hand, acacia gum acts as a binder in tablets by imparting high mechanical strength but prolonged disintegration time. Development of a co-processed excipient involving combination of the two excipients at sub-particle level will improve the functionality of the final product. Objective: To develop a direct compressible co-processed excipient with pregelatinized cocoyam starch and acacia gum and to evaluate its compaction behavior and tableting properties in metoprolol succinate tablets. Material and Methods: Batches of the co-processed excipient were prepared by co-fusion using different ratios (97.5:2.5; 95:5; 92.5:7.5; 90:10; 85:15; 80:20) of pregelatinized cocoyam starch and acacia gum. Flow and compaction properties and Fourier transform Infrared (FT-IR) analysis were carried out on native and pregelatinized starches and on the co-processed excipients. Metoprolol succinate tablets were formulated by direct compression using selected batches of co-processed excipients, pregelatinized cocoyam starch and acacia gum and then evaluated for mechanical strength and drug release. Results: Pregelatinization produced starch with larger granules (138.75±59.21µm), improved swelling (2.03±0.00) and flow (flow rate 0.52±0.03g/s). The FTIR analysis of the co-processed excipients confirmed absence of chemical interaction. Flow properties, compressibility (Kawakita value, a = 0.190 – 0.223) and rate of packing (Consolidation rate, K = 0.1221 – 0.2551) of the co-processed excipients were enhanced. Metoprolol succinate tablets containing the co-processed excipients had higher mechanical strength (Crushing strength 106.03±15.80 MNm-2) than those containing starch alone but faster drug release (disintegration time 1.80 ±0.20 -5.75±0.25; dissolution time; t80 30-50 min) than those containing acacia gum. Cocoyam starch: acacia gum ratio 97.5:2.5 gave the optimum formulation with high crushing strength (106.03 ± 15.8MNm-2) and fast release (t80 = 30 min). Conclusion: Co-processed excipients of pregelatinized cocoyam starch and acacia gum could serve as suitable alternatives to other directly-compressible excipients for the formulation of tablets.